Color Characteristics and Stability of Anthocyanin in Fresh Thunbergia erecta Flower Extract - Marpaung, Abdullah Muzi; Ramdhani, Rizal Pauzan (Indonesian Journal of Natural Pigments, 2020)
The main purpose of the present research was to evaluate the color characteristics of anthocyanin in Thunbergia erecta flower extract at various pH to know its potentiality as a food colorant. The fresh petal was macerated in 0.1 N HCl-Ethanol 96% (1:9) for an hour, filtrated and diluted in a buffer solution pH 1 to 12, then scanned by a spectrophotometer at 400 – 700 nm. The extract was almost colorless at pH 4 to 6 and show extremely low color stability at pH 7 and 8 (the half-life was 6.69 and 16.66 minutes, respectively). In contrast, the extract was very stable at pH 3. There was no significant color decrease after the extract being stored for 14 days at pH 3. An important spectral characteristic of Thunbergia erecta flower extract appeared at pH 7 to 10 by showing all the three colored species of anthocyanin. At pH 8, the red flavylium cation detected as λshoulder at around 537 nm, the purple quinonoidal base as the λpeak at 577 nm and blue anionic quinonoidal base as the λpeak at 614 nm. The unique spectral characteristic promoted the Thunbergia erecta flower as a potential anthocyanin-source to be used in the study of anthocyanin transformation in an aqueous system.